Body mass index and vitamin D level in carpal tunnel syndrome patients - Nageeb, Rania S. (Egypt J Neurol Psychiatr Neurosurg, 2018)
BACKGROUND: Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy of the upper extremity. The aim of this study is to evaluate the body mass index (BMI) and vitamin D levels in CTS patients. METHODS: The current study was conducted at Zagazig University Hospitals. It included 50 CTS patients and 50 controls. Clinical assessment was carried out to exclude symptoms and signs of neuropathy. Laboratory investigations including vitamin D levels, glycosylated hemoglobin, liver, and kidney function were carried out for every participant. All patients underwent electrodiagnostic study and completed Boston questionnaire to assess their pain sum score, symptom severity (SSS), and functional status (FSS). RESULTS: Patients had significantly higher BMI and lower vitamin D levels compared to controls (p = 0.003 and p = 0.001, respectively). Those with severe CTS had a significantly higher BMI and lower vitamin D levels than the others (p = 0.03 and p = 0.01 respectively). No significant difference was found between CTS subgroups regarding the SSS, while a higher significant FSS and pain sum score were reported in the severe CTS patients compared to the other two groups (p = 0.01 and p = 0.04 respectively). A significant negative correlation was detected between vitamin D levels and both of BMI, and Boston pain sum scores (p = 0.01 and p = 0.03 respectively). Also, an inverse correlation was detected between vitamin D levels and both of SSS and FSS (p = 0.14, p = 0.06). Furthermore, a significant positive and negative correlation between vitamin D levels and both of conduction velocity and distal motor latency respectively was observed (p = 0.02 and p = 0.01 respectively). CONCLUSIONS: Carpal tunnel syndrome was significantly associated with hypovitaminosis D especially in patients with higher BMI. This highlights the importance of vitamin D supplements and weight loss regimes to minimize the severity of their pain.